Acondicionamiento de módulo de generación fotovoltaico en la UAN sede Manizales para carga de dispositivos móviles e iluminación (2022)
In past semesters, a photovoltaic charging module for mobile devices has been developed at UAN Manizales. Currently this module is not functional, a diagnosis and a corrective maintenance plan is performed,as well as a redesign of the current components in order to improve the characteristics of the module and adjust them to a new set of requirements of load and photovoltaic potential.